Ligand-Based Drug Design of Genipin Derivatives with Cytotoxic Activity against HeLa Cell Line: A Structural and Theoretical Study - Diana López-López; Rodrigo Said Razo-Hernández; César Millán-Pacheco; Mario Alberto Leyva-Peralta; Omar Aristeo Peña-Morán; Jessica Nayelli Sánchez-Carranza; Verónica Rodríguez-López (MDPI AG, 2023)
Cervical cancer is a malignant neoplastic disease, mainly associated to HPV infection, with high mortality rates. Among natural products, iridoids have shown different biological activities, including cytotoxic and antitumor effects, in different cancer cell types. Geniposide and its aglycone Genipin have been assessed against different types of cancer. In this work, both iridoids were evaluated against HeLa and three different cervical cancer cell lines. Furthermore, we performed a SAR analysis incorporating 13 iridoids with a high structural similarity to Geniposide and Genipin, also tested in the HeLa cell line and at the same treatment time. Derived from this analysis, we found that the dipole moment (magnitude and direction) is key for their cytotoxic activity in the HeLa cell line. Then, we proceeded to the ligand-based design of new Genipin derivatives through a QSAR model (R2 = 87.95 and Q2 = 62.33) that incorporates different quantum mechanic molecular descriptor types (<semantics>ρ</semantics>, <semantics>ΔPSA</semantics>, <semantics>∆Polarizability2</semantics>, and <semantics>logS</semantics>). Derived from the ligand-based design, we observed that the presence of an aldehyde or a hydroxymethyl in C4, hydroxyls in C1, C6, and C8, and the lack of the double bond in C7-C8 increased the predicted biological activity of the iridoids. Finally, ten simple iridoids (D9, D107, D35, D36, D55, D56, D58, D60, D61, and D62) are proposed as potential cytotoxic agents against the HeLa cell line based on their predicted IC50 value and electrostatic features.